마틴 마르지엘라의 패션에 내재된 생태미학 관점에서의 지속가능한 디자인 접근법 해석 - 전유미; Yu Mi Chon; 배정민; Jung Min Bae (기초조형학연구, 2015)
본 연구는 지속가능한 디자인의 논의가 생태학적 담론의 수용으로 변화되어 가는 이론적 배경을 근거로, 지속가능성과 생태미학의 개념을 결합하여 실질적으로 적용할 수 있는 지속가능한 디자인 접근법을 도출하고자 하였다. 그리고 이러한 접근법이 반영된 지속가능한 패션이 어떠한 내적의미와 표현특성을 가지는지 분석하기 위하여, 도출한 접근법을 사회문화적 이슈와 디자인 철학이 뚜렷하게 표출된 마틴 마르지엘라의 패션에 대입하여 해석하였다. 본 연구의 결과는 다음과같다. 첫째, 지속가능 디자인을 생태, 디자인, 미학의 영역에서 통합적으로 분석하기 위해 제시된 생태미학은 자연을 생태적 관점에서 미의 대상으로 바라보고 아름다움의 의미를 재정립한다. 둘째, 생태미학 관점을 적용한 지속가능한 디자인은 성장과 진화의 가시화, 노화의 수용과 의도적 낡음의 이미지 표현, 사용흔적을 통한 내러티브 부여, 생태체험요소 제공과 참여유도의 접근법으로 구체화할 수 있다. 셋째, 이 접근법들을 마르지엘라의 패션에 대입하여 상응하는 특성을 분석한 결과, 제작과정의 노출, 노화된 소재와 화이트 페인트, 사용흔적과 역사의 전이, 메시지 전달과 사용자의 주체성 등을 내외적 특성으로 도출할 수 있었다. 본 연구의 과정과 결과는 지속가능 디자인의 접근법을 다양화하고 구체화하기 위한 시도로서, 향후 창의적인 지속가능 디자인 방법론의 개발 및 확립, 지속가능한 패션 해석의 새로운 이론적 프레임 구축에 이바지할 것으로 기대된다. This study aimed to draw practically applicable sustainable design approaches by combining the concepts of sustainability and ecological aesthetics on the basis of the theoretical background that the subject of sustainable design was embracing ecological discourses. In addition, the oeuvre of Martin Margiela, who revealed a clear stance on socio-cultural issues and his design philosophy, was interpreted with reference to the derived approaches in order to discover the internal meanings and expressive qualities of sustainable fashion. The outcomes of this study are as follows. First, the ecological aesthetics integrates ecology with design and aesthetics to propose an analytical frame and views the nature as the subject of beauty redefining an aesthetic category. Secondly, the ecological viewpoint reflected in sustainable design materialized through four detailed methods: visualization of growing and evolving, acceptance of aging, presentation of intentionally over-worn images, impartment of a narrative by exposing signs of being used, and provision of elements that lead to ecological experience and participation. Thirdly, as a result of interpreting Margiela’s fashion based on the aforementioned four approaches, several expressive traits embodying sustainability from an ecological aesthetics perspective were recognized: revealing the process of garment making, utilizing aged material and white paint, transferring vestiges of former users as well as history, delivering messages and establishing user``s identity. Consequently, the process and the result of this study is an attempt to diversify and definitize the sustainable design approaches. It is confidently expected that this study cannot only contribute to the development and establishment of creative sustainable design methodologies, but also provide follow-up studies with an inventive theoretical framework for the analysis on sustainable fashion.